1984
DOI: 10.1227/00006123-198402000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Extracavitary Approach to the Spine for Thoracic Disc Herniation: Report of 23 Cases

Abstract: Twenty-three patients were operated upon for thoracic disc herniation between 1973 and 1982. The lateral approach to the vertebral column was used in each. Most patients had severe local pain; 13 had severe myelopathy or complete motor paralysis, including 4 who had become paraplegic after laminectomy. Eleven patients had calcified discs or osteophytic ridges. Air myelography and computed tomography were diagnostic in all cases. Postoperatively, 17 patients achieved significant relief of pain, 20 improved neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0
7

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(93 citation statements)
references
References 0 publications
1
85
0
7
Order By: Relevance
“…The predominant central location of HTHD in this series is consistent with literature findings [2,3,15,16,30]. For this reason, even posterior approaches enlarged with a costotransversectomy should be prohibited for this type of lesion [5,16,21,22,24,26,27]. Regarding a series of 15 surgical revisions after thoracic discectomy, Dickman et al found 13 calcified central herniated discs and stressed the importance of the anterolateral approach to this type of lesion for a complete excision with less risk of neural injury [16].…”
Section: Discussionsupporting
confidence: 87%
“…The predominant central location of HTHD in this series is consistent with literature findings [2,3,15,16,30]. For this reason, even posterior approaches enlarged with a costotransversectomy should be prohibited for this type of lesion [5,16,21,22,24,26,27]. Regarding a series of 15 surgical revisions after thoracic discectomy, Dickman et al found 13 calcified central herniated discs and stressed the importance of the anterolateral approach to this type of lesion for a complete excision with less risk of neural injury [16].…”
Section: Discussionsupporting
confidence: 87%
“…There is no gold standard approach and each technique has unique advantages and disadvantages [7,8]. These approaches include transpedicular, transfacet pedicle-sparing approaches, costotransversectomy, transthoracic transpleural approach, thoracoscopic approach [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This technical advantage has led to excellent neurological outcomes with nearly 75% of patients described in the literature demonstrating neurological improvement. 1,8,9,16,20,21 Furthermore, Maiman et al reported significant neurological improvement following late anterior decompression with restoration of a normal anatomical relationship of the spinal cord and spinal canal using the LECA in patients previously treated with laminectomy or spinal instrumentation, or both. 20 Pain associated with thoracolumbar pathology also tends to respond well to the LECA, with approximately 85% of patients experiencing meaningful relief.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven of the 63 articles (62 from the PubMed search, 1 from manuscript citations) were included in the LECA Summary Table (Table 1). 1,4,8,9,14,16,[19][20][21][22]26 The LECA Summary Table (Table 1) details the included studies. Study design, class of medical evidence, number of patients, levels of pathology, type of pathology, neurological outcome, pain outcome, and complications were included when mentioned in the original text.…”
Section: Systematic Reviewmentioning
confidence: 99%